THE REASONS OF JAPAN'S CLAIM ON DOKDO ISLAND - Ikhya'ul Khasanah (2011)
This undergraduate thesis tried to discuss about the territorial dispute over Dokdo. Dokdo is a group of tiny islands in the East Sea / Sea of Japan disputed by Japan and South Korea. At this time, Dokdo is under the administration of South Korea. However, Japan still insists on claiming Dokdo as its territory. In the end of this research, there are at least three reasons why Japan still insists on claiming Dokdo. The first reason is the economic value of Dokdo. Dokdo has at least two high eco